Centralidade e impactos regionais de política monetária: um estudo dos casos brasileiro e espanhol - Fernanda Faria Silva (2011)
This study is based on the consideration that money is not neutral in space and it plays an important role in the formation and perpetuation of regional inequalities. This work aims to investigate the application of the impact of monetary policy on different regions of Brazil and Spain. The main point is to analyze the role that the centrality plays in terms of mitigating or enhancing the effects of the monetary transmission mechanism, a focus which is still not very explored in the economical literature. This work is based on the Post Keynesian monetary theory, which considers the importance of the structural and behavioral effects (associated with different liquidity preferences and stages of financial development), in the aim to explain the regional differences generated from the common monetary shocks. After an explication about the historical reconstruction of the conformation standards of centralities in the analyzed countries, the study is followed by a recent categorization of these patterns. An empirical research was made analyzing the regional effects of monetary policy and the sources of asymmetry in the transmission of shocks. In this study, it was found that monetary shocks are propagated more intensely in the peripheral states and autonomous communities, which are characterized by weaker economic structures, and a greater dependence on the dynamics of the central regions and higher potential of instability. These effects cause a rise in the liquidity preference of the agents. It was identified that one of the consequences of these impacts is the existence of spatially differentiated interest rates. Furthermore, the structural and financial characteristics of the regions play an important role in explaining the asymmetry in the transmission of monetary shocks. Finally, it is important to emphasize that the main contribution of this work is the consideration that the construction of space is an important element to understand the impacts of monetary policy and, in this sense, the centrality plays a important role to empower and strengthen these impacts, highlighting regional disparities.